Improving HPV vaccine acceptance through peer-to-peer education among adolescent girls in the urban poor settings of Kisenyi, Kampala, Uganda. - Doreen Tuhebwe; Christine Adyedo; Emmanuel Ahumuza; Steven Ssendagire; Rhoda K Wanyenze (PLOS Global Public Health)
In Uganda, cervical cancer due to Human Papilloma Virus (HPV) is the most prevalent cancer among women. In 2015, the HPV vaccine was introduced into Uganda's EPI program, targeting young girls in-and out-of-school. However, HPV vaccine uptake remains low at 44% for the second dose with disparities in vulnerable populations in urban poor settings. We piloted a peer-to-peer education approach in the urban slums of Kisenyi in Kampala, Uganda to address vaccine hesitancy among adolescent girls aged 9-13years. In 2019/2020, a total of 18 girls between the ages of 10-15 years old, who had previously received two doses of the HPV vaccine were trained as Adolescent Peer Educators (APEs), co-created an HPV vaccine health education message, and conveyed it to unvaccinated peers, with the intention of increasing vaccine uptake. The APEs attended weekly mentorship meetings with the intervention team to document their experiences and be supported to link interested peers to the nearest public health facility for vaccination. Over a 12-week period, the APEs identified 192 unvaccinated peers aged 10-13years, 177/192 were provided with the health education messages, 145/177 expressed willingness to receive the first dose of the vaccine and 88/145 (60.7%) received it. Through repeat socialization, positive influence and friendship, the APEs were able to communicate the benefits of the HPV vaccine, manage fears like anticipation of injection pain and connect interested peers to the community health workers (CHWs) for health facility linkage. A common barrier experienced by APES was the fact that caretakers made the final decision even after their daughters expressed interest requiring CHW intervention with caretakers. Peer-to-peer education and linkage to vaccination is a feasible approach that could increase uptake of HPV vaccine among adolescents. We recommend larger scale effectiveness studies to refine the model and include a comparison group to identify the optimal intervention components.